Q&A with Ping Gao - Ping Gao (Cell Reports)
Ping Gao, guest editor of the cancer metabolism special issue, spoke with Cell Reports about his scientific interests and his lab’s focus on investigating the metabolic reprogramming in cancer cells and immune cells in the tumor microenvironment. Ping also discussed recent developments and future directions in the field.